2014
DOI: 10.1186/1471-2458-14-1293
|View full text |Cite
|
Sign up to set email alerts
|

Spicy food consumption is associated with adiposity measures among half a million Chinese people: the China Kadoorie Biobank study

Abstract: BackgroundFew animal experiments and volunteer-based intervention studies have showed a controversial effect of spicy foods on weight management; however, information is scant on the association between spicy food intake and obesity. This study aims to examine the impact of spicy food on quantitative adiposity measures in the Chinese population; a population with a low prevalence of general obesity, but a high prevalence of central obesity.MethodsA total of 434,556 adults (255,094 females), aged 30–79 years, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
53
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 37 publications
12
53
1
1
Order By: Relevance
“…Los datos de otro estudio (19) indican que el consumo de comida picante es un factor de riesgo para la obesidad en la población adulta de China, especialmente para la obesidad abdominal en los hombres, pero se necesitan más estudios para dilucidar los mecanismos que subyacen a esta asociación.…”
Section: Discussionunclassified
“…Los datos de otro estudio (19) indican que el consumo de comida picante es un factor de riesgo para la obesidad en la población adulta de China, especialmente para la obesidad abdominal en los hombres, pero se necesitan más estudios para dilucidar los mecanismos que subyacen a esta asociación.…”
Section: Discussionunclassified
“…However, the epidemiological evidence does not portray a clear picture. As shown by a recent big epidemiological study from China, ‘spicy food’ was, quite unexpectedly, positively associated with body weight (Sun et al ., ). In Chinese cuisine, spicy food is more meat‐based rather than vegetable‐based with heavy salt and/or oil use for flavour and palatability, the primary spice being hot pepper ( Capsicum spp.).…”
Section: The Introduction Of Cannabimimetic Spices During Agriculturementioning
confidence: 97%
“…Over the past several decades, many studies have been conducted to explore the effects of spicy food and their bioactive ingredients such as capsaicin. Although some previous studies have shown bene cial effects of spicy food consumption on obesity and other chronic diseases [11,[14][15][16], there are inconsistent results of the association between spicy food intake and obesity have been reported in animal and human intervention studies [17,18]. The China Kadoorie Biobank (CKB) study found that spicy food consumption was positively associated with BMI and other adiposity measures among half a million Chinese people [19], Our previous also found spicy avor, spicy food intake frequency was positively associated with general obesity [20].…”
mentioning
confidence: 99%